Sociological and anthropological methods in old testament study - Herion, Gary A. (Old Testament essays, 1987)
Old Testament scholarship has appealed to the social sciences mainly due to a concern to reconstruct the history of Israel in its relationship to neighbouring cultures. The contribution of social science in the process of reconstructing the material culture as well as the religion of ancient Israel, is discussed. For the reconstruction of the former, the historian is urged to give methodological priority to non-biblical documents and archaeological finds rather than to the old Testament, due to the biased and partial nature of the latter. A reconstruction of the religion of old Israel is hardly free from modern Western interpretation and ideological biases fortified by the social sciences. The article pleads for free interaction between historical data and sociological models without the one having meaning in terms of the other.